Spatial and temporal dynamics of phytoplankton primary productivity in Chinese reservoirs: influencing factors and carbon sequestration - Deng, Haojun; Zheng, Zhuangpeng; Cai, Qun; Wu, Jingyi; Chen, Aimin (Frontiers in Environmental Science, 2025)
Phytoplankton primary production (PP) underpins the sustainability of aquatic ecosystems in reservoirs. However, national-scale studies of reservoir phytoplankton PP in China remain limited, typically subsumed within lake research, hindering mechanistic understanding of large-scale PP variations. To address this gap, we compiled a database of phytoplankton PP in Chinese reservoirs (1980–2023) based on an exhaustive literature review, incorporating only data measured using the light-dark bottle method. Utilizing this database, this study quantifies phytoplankton PP and carbon sequestration potential across 165 Chinese reservoirs. The result showed that phytoplankton PP ranged 0.13–10.22 g O2·m−2·d−1, with significantly higher values in the Yellow River (YR), Songhua River and Liaohe River (S/LR), and Haihe and Huaihe River (H/HR) basins versus the Pearl River (PR), Northwest Internal Rivers (NIR), and Southwest Rivers (SWR) basins. Temporally, phytoplankton PP peaked in the 1990s, declined thereafter, but rebounded in the 2020s (decadal sequence: 1990s > 2020s > 2000s > 1980s > 2010s). Seasonal variation followed summer > spring > autumn > winter. Sunshine hours, water depth, and rainfall emerged as dominant phytoplankton PP drivers. National phytoplankton PP extrapolation reached 22.08 Tg⋅O2⋅a−1 (1 Tg = 1012 g), equivalent to 6.62 Tg carbon sequestration capacity. Our analysis delineates spatio-temporal patterns of phytoplankton PP in Chinese reservoirs and underscores its significance for regional carbon budgets and aquatic ecosystem dynamics.